Application specifics of nonequilibrium phase behavior models in the development of hydrocarbon deposits: a critical review - O. A. Lobanova; I. M. Indrupskiy (Georesursy, 2024)
In order to correctly model the fluid phase behavior and accurately account for phase compositions, fractions and properties in the reservoir during the hydrocarbon field development, it is necessary in some cases to use non-equilibrium phase behavior models.The signs of non-equilibrium phase behavior of hydrocarbons observed during field development may be associated with various factors. It has been experimentally shown that the so-called “thermodynamic non-equilibrium” behavior (when the phase transition cannot be considered instantaneous compared to the characteristic rate of change of the system state parameters) manifests itself due to the limited specific area of the phase interface. “Hydrodynamic non-equilibrium” behavior (the difference in actual fractions of the produced phases from the expected ones) is observed at high production rates for the reason that one of the phases does not have enough time to segregate and is transported as an aerosol in the second phase, without forming a separate continuous medium. Proper identification of the type of non-equilibrium behavior is a key factor in choosing the correct model.The paper considers specifics of various models to account for non-equilibrium phase behavior. Examples of their practical application are analyzed for various manifestations of non-equilibrium phase behavior and different causes of its occurrence. The problem of modeling fluid flow with non-equilibrium phase transitions is discussed.